2024
DOI: 10.1039/d3sc05275c
|View full text |Cite
|
Sign up to set email alerts
|

Using waste to treat waste: facile synthesis of hollow carbon nanospheres from lignin for water decontamination

Xiang Liu,
Zixuan Hao,
Chen Fang
et al.

Abstract: Herein, a new type of hollow carbon nanospheres (HCNs) is designed and synthesized by pyrolysis of biomass dealkali lignin, as an efficient nanocatalyst for the elimination of antibiotics in complex water matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Liu et al also reported spatial confinement of Co 3 O 4 nanoparticles into carbon nanotubes for degradation of bisphenol A via a dominated nonradical pathway . As part of our group’s recent studies on nanoconfined heterogeneous catalytic systems for water decontamination, in this work, we reported confinement of Co nanoparticles in N-doped carbon nanorods (Co-NCNRs), by encapsulating Co nanoparticles into N-doped carbon nanorods, in activating for antibiotic degradation. First, Co-NCNRs were pyrolyzed from pullulan, dopamine hydrochloride, and Co­(NO 3 ) 2 at 550 °C in air for 3 h. Then, the nanostructure and nanomorphology of Co-NCNRs were fully investigated by various physical characterizations.…”
Section: Introductionmentioning
confidence: 68%
“…Liu et al also reported spatial confinement of Co 3 O 4 nanoparticles into carbon nanotubes for degradation of bisphenol A via a dominated nonradical pathway . As part of our group’s recent studies on nanoconfined heterogeneous catalytic systems for water decontamination, in this work, we reported confinement of Co nanoparticles in N-doped carbon nanorods (Co-NCNRs), by encapsulating Co nanoparticles into N-doped carbon nanorods, in activating for antibiotic degradation. First, Co-NCNRs were pyrolyzed from pullulan, dopamine hydrochloride, and Co­(NO 3 ) 2 at 550 °C in air for 3 h. Then, the nanostructure and nanomorphology of Co-NCNRs were fully investigated by various physical characterizations.…”
Section: Introductionmentioning
confidence: 68%
“…44) to produce ·OH (ref. 45–47) (eqn (3)). Meanwhile, visible-light irradiation promoted the reaction of H 2 O 2 with the ·OH radical to yield ·O 2 − (eqn (4)).…”
Section: Resultsmentioning
confidence: 99%